Dynamic impedance spectroscopy using dynamic multi-frequency analysis: A theoretical and experimental investigation. (20th August 2017) - Koster, Dominique; Du, Guoqing; Battistel, Alberto; La Mantia, Fabio
Abstract: Dynamic impedance spectroscopy is a powerful tool to investigate the temporal development of reaction kinetics in electrochemical systems, where the reactive species may undergo irreversible changes during the measurement. In this work we redefined dynamic impedance based on quadrature filters and underwent an analysis of multisine waveforms for the measurement of the dynamic impedance spectra during cyclic voltammetry. We proposed a quasi-triangular wave in order to minimize the interactions between the dc and ac signals. We showed on both simulated and experimental data that a proper design of the multisine wave allows accessing spectra with large number of frequencies and quasi-triangular waves with high values of scan rate. The key point is the frequency distribution of the multisine, optimized according to the implicit time variation of the system. Moreover, we quantify the non-linear artifacts as a function of both multisine amplitude and number of frequencies. Backed up by numerical simulation, we show how to recover simultaneously high quality impedance spectra and pristine voltammograms.